Broad spectrum micronutrients: a potential key player to address emotional dysregulation - Villagomez, Amelia; Cross, Michelle; Ranjbar, Noshene (Frontiers in Child and Adolescent Psychiatry, 2023)
Psychiatric conditions are inherently multifactorial and must be understood and addressed within a multidimensional framework. Adequate nutritional intake is necessary for optimal mental health and is thus an essential component of any psychiatric treatment plan; this is especially true as many patients have a diet high in ultra-processed foods. However, due to a variety of factors such as individual biological and behavioral contributors, modern farming practices, and climate change, implementing a healthy diet alone may not be sufficient to satisfy nutritional requirements. Research studies on three formulations of broad-spectrum micronutrients (BSMs) have demonstrated significant efficacy in treating a range of mental health disorders. In particular, outcomes associated with emotional regulation via BSMs across a variety of psychiatric illnesses (ADHD, autism, trauma, mood disorders, nicotine dependence, and psychosis) to date have been positive.